Prompt before the choice is made: effects of a stair-climbing intervention in university buildings. - Lewis, A; Eves, F (2012)
OBJECTIVES:   Recent interventions report positive results following a multi-component campaign to increase stair climbing. This study investigated the effectiveness of volitional and motivational components of a stair-climbing intervention in the workplace. Design.  Interrupted time-series design. METHODS:   Ascending stair/lift choices, coded by gender, were observed between 08:00-10:00 and 14:15-16:15 on weekdays, in four university buildings (n = 14,138; 46% female). Baseline observations (stage 1; 5 days) preceded a motivational intervention, that is, a poster positioned inside the lift(s), that was positioned in each building (stage 2; 5 days). Next a volitional intervention, that is, point-of-choice prompt, supplemented the motivational one (stage 3; 8 days). Logistic regression analysis of stair/lift choices included the independent variables of intervention components, gender, time of day, building height, number of lifts, and pedestrian traffic. RESULTS:   There was no significant change in stair climbing when the motivational component was positioned alone (Odds Ratio [OR] = 0.93, 95% Confidence Interval [CI] = 0.85-1.02, p = .123). In contrast, stair climbing increased significantly when the volitional component, that is, the point-of-choice prompt, was added (OR = 1.23, 95% CI = 1.14-1.32, p < .001). During both stages, building height, number of lifts, time of day, and pedestrian traffic were all associated with stair climbing. No significant gender effects were seen. CONCLUSIONS:   A motivational component positioned alone, inside the lift(s) did not increase stair climbing. When a volitional component was added, that is, point-of-choice prompt positioned at the time and place where individuals choose their method of ascent, stair climbing increased significantly. Visibility of a prompt at the time behavioural choice is made appears necessary to change actual behaviour.